Exploring new frontiers of education using humanoid robots – a case study of patient centred innovation in digital health education. Issue 1 (2nd January 2022) - Connolly, Cornelia; Walsh, Jane C.; Worlikar, Hemendra; Ryan, Leona; Murray, Aoife; O'Connor, Sadhbh; Kelly, Jack; Coleman, Sean; Vyas Vadhira, Vijay; Newell, Elaine; O'Keeffe, Derek T.
ABSTRACT: Digital education is intertwined with matters of global economics, geopolitics, as well as ongoing changes in what counts as knowledge, skills and learning. We have witnessed throughout the COVID-19 pandemic how technology has been embraced within education from online classes to innovative mobile learning approaches and evaluating humanoid robots in education is the next step. Driven by a need to keep pace with the evolving techno- and socio-economic requirements, schools and society are increasingly adopting artificial intelligence (AI) and robots in their daily activity. This paper presents a feasibility case study in digital health education where a humanoid robot was chosen to teach based on its form and function. With an imperative to establish a strong and sustainable learning space, the aim of this paper is to present results and learn about the future of digital health education from humanoid robots being deployed in digital health learning spaces. The paper concludes by highlighting key design challenges in unbundling educational approaches in the context of humanoid robots. It is intended that the outcomes of this paper will extend beyond the COVID-19 pandemic by contributing to the humanoid robot technology discussion that will push towards more futuristic artificial intelligence in and for education.